(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Economic growth is a key indicator of a country’s welfare and level of socio-economic development. This article examines Thailand’s economic growth over the past few decades. It analyses the factors contributing to growth and possible constraints, and suggests ways to develop the economy in the face of global challenges. The study uses empirical analysis based on official data and academic literature. It focuses on the role of investment, tourism, foreign trade and government policies in the sustainable growth of the Thai economy.